Mountains of Blame : Climate and Culpability in the Philippine Uplands - Smith, Will; Smith, Will (Book collections on Project MUSE., 2021)
"This thoughtful ethnography provides a detailed account of a forest community on the Philippine island of Palawan grappling with the material and conceptual implications of a changing climate, including residents' sense of self-blame for environmental events. Swidden agriculture has long been considered the primary cause of deforestation throughout Southeast Asia. Following this logic, government authorities excluded the Indigenous people of Palawan from their ancestral lands after World War II and forced them to abandon traditional modes of land use. After adopting ostensibly modern and ecologically sustainable livelihoods, they have experienced drought and uncertain weather patterns, which they have blamed on their own failure to observe traditional social norms that are believed to regulate climate. Such norms, including local customary modes of punishment for violators of incest taboos and other transgressions, have, like swidden agriculture, been outlawed by the Philippine state. In Mountains of Blame, Will Smith uses historical records and over twelve months of ethnographic fieldwork to examine statements about changing weather, processes of dispossession, and experiences of climate-driven hunger that are related to Pala'wan narratives of self-blame, a personal response to climate change that is not uncommon among Indigenous peoples worldwide. He suggests that reckoning with these complexities requires questioning key assumptions in the global environmental policy narrative"